Inkblot personality test understanding the unconscious mind - Dubey, Bankey Lal 1943-; Banerjee, Padmakali; Dubey, Anand (SAGE Publications Pvt Ltd, 2020)
First authoritative and comprehensive study in the field of Inkblot Personality Test, this book describes the historical roots of the three major projective inkblot measures: the Rorschach, the Holtzman Inkblot Technique (HIT) and the Somatic Inkblot Series (SIS). It presents the extensive psychometric background work accompanying the normative data and diagnostic indicators along with indices for selecting executives in a business organization. The book begins with a detailed history of Hermann Rorschach and his early experiments with inkblots in the diagnosis of mentally ill patients. Special attention is given to the administration and scoring of the Rorschach, with the sections detailing the systems developed by Klopfer and Exner. The HIT and SIS are also reviewed in detail, emphasizing their psychometric qualities